2021
DOI: 10.1117/1.jbo.26.5.056004
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualization of renal microperfusion using laser speckle contrast imaging

Abstract: . Significance: Intraoperative parameters of renal cortical microperfusion (RCM) have been associated with postoperative ischemia/reperfusion injury. Laser speckle contrast imaging (LSCI) could provide valuable information in this regard with the advantage over the current standard of care of being a non-contact and full-field imaging technique. Aim: Our study aims to validate the use of LSCI for the visualization of RCM on ex vivo perfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“… 23 It has also been reported to be capable of imaging renal cortical microperfusion in porcine kidney transplantation. 24 Despite the accumulated research and clinical evidence, it has not translated to clinical use in kidney or kidney-pancreas transplantation so far.…”
Section: Discussionmentioning
confidence: 99%
“… 23 It has also been reported to be capable of imaging renal cortical microperfusion in porcine kidney transplantation. 24 Despite the accumulated research and clinical evidence, it has not translated to clinical use in kidney or kidney-pancreas transplantation so far.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation of renal blood flow with stream dark-field imaging was superior to that with LSCI in 1 study. [24]…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation of renal blood flow with stream dark-field imaging was superior to that with LSCI in 1 study. [24] Because LSCI is a dyeless visualization technology, it can be used in its different modes multiple times during the same procedure without any interference to its field of view. It also provides an objective relative quantification of flow and perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Despite extensive research on LSCI, few studies have explored its potential as kidney quality assessment tool. The only study that has used LSCI to measure the kidney during NMP, conducted by Heeman et al 12 showed that onesided measurement can assess cortical microcirculation and detect perfusion deficits. However, it is unknown whether there is heterogeneity of microcirculation between the ventral and dorsal aspects.…”
Section: Introductionmentioning
confidence: 99%